Purification and properties of a 75-kilodalton major protein, an immunodominant surface antigen, from the oral anaerobe Bacteroides gingivalis. - Yoshimura, F (1989)
A 75-kilodalton major protein (75K protein) was purified to homogeneity from the cell lysate fraction and the envelope of Bacteroides gingivalis 381. The 75K protein was originally present in the outer membrane or the outermost part of this organism as a large, stable complex with an apparent molecular weight of about 2,000,000. Heating at 80 degrees C and at higher temperatures in the presence of sodium dodecyl sulfate was needed to completely dissociate it to monomers. Amino acid analysis revealed that the 75K protein had about 50% nonpolar amino acids. Various strains of B. gingivalis but not other bacteria, including oral Bacteroides species tested, contained serologically related 75K proteins when tested in Western blotting (immunoblotting) analysis. The abundance and localization of the 75K protein in this organism suggest that it has the potential to participate in the host-parasite interaction in infection. The 75K protein was, indeed, strongly recognized in patients with adult periodontal diseases. Immunoblotting with sera from patients and with rabbit antisera generated by intravenous inoculations of whole B. gingivalis cells revealed that the 75K protein was an immunodominant antigen on the surface of B. gingivalis.